Nosocomial outbreak caused by Scedosporium prolificans (inflatum): four fatal cases in leukemic patients. - Alvarez, M (1995)
Four cases of fatal disseminated Scedosporium prolificans (inflatum) infection occurring in neutropenic patients are reported. Because of hospital renovation, the patients were cared for in a temporary hematologic facility. S. prolificans (inflatum) was isolated from blood cultures of these four patients, two of whom underwent full necropsy, and revealed abundant vegetative hyphae and ovoid conida with truncate bases in many organs. In vitro susceptibility testing of fungal strains showed all isolates to be resistant to amphotericin B, flucytosine, miconazole, ketoconazole, fluconazole, and itraconazole, with MICs greater than 16 micrograms/ml. The reported infections, two in each of two rooms, occurred over a period of 1 month, with very similar clinical outcomes. Circumstancial evidence suggested a nosocomial outbreak, but the environmental samples collected from the rooms, corridors, and adjacent areas did not yield S. prolificans (inflatum). Nevertheless, circumstantial evidence suggested a nosocomial outbreak of S. prolificans (inflatum) infection.